Perbandingan Sistem Kepegawaian Di Indonesia Dan Jepang - Sintia Kartini Haniandaresta; Nadia Wulandari; Siti Sobariyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
One of the discussions on the comparison of public administration is about the comparison of staffing system. This journal discusses a comparison between the Indonesian and Japanese staffing systems in the recruitment, promotion and rotation system. This aims to deepen knowledge related to the civil service system both in Indonesia and in Japan and to find some good lessons for the civil service system in Indonesia. This study uses a type of literature review and secondary data sources that describe theories and information both past and present.